Testing General Relativistic Predictions with the LAGEOS Satellites. (22nd May 2014) - Peron, Roberto
Abstract : The spacetime around Earth is a good environment in order to perform tests of gravitational theories. According to Einstein's view of gravitational phenomena, the Earth mass-energy content curves the surrounding spacetime in a peculiar way. This (relatively) quiet dynamical environment enables a good reconstruction of geodetic satellites (test masses) orbit, provided that high-quality tracking data are available. This is the case of the LAGEOS satellites, built and launched mainly for geodetic and geodynamical purposes, but equally good for fundamental physics studies. A review of these studies is presented, focusing on data, models, and analysis strategies. Some recent and less recent results are presented. All of them indicate general relativity theory as a very good description of gravitational phenomena, at least in the studied environment.